(NpISXMA(B. (NmATERIALY DLQ BIOGRAFII(B: [1840-1877] / s (N~ASTX (B8s - (NnEKRASOW(B, (NnIKOLAJ aLEKSEEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1967)
(Nw WOSXMOJ TOM WO[LI PISXMA(B, (NMATERIALY DLQ BIOGRAFII (B1840-1877 (NGG(B.s
rus
Keywords: (NpISXMAs; (NbIOGRAFIQs